Jacques Polieri: Kinetic Theatre Space - Juan Ignacio Prieto López (VLC Arquitectura)
Between the First and Second World War the definition of the new type of theater building was one of the main tasks of the European Avantgarde. In its design and theoretical formulation were poets, playwrights, theater directors, architects, painters, actors, engineers… from different countries and art movements. Despite the collaboration of the leading members of the Avant-garde like Marinetti, Moholy-Nagy, Kiesler, El Lissitzky, Gropius… none of these proposals were built because of their radical and utopian characteristics. It was a young French theater director, Jacques Polieri, who became the main compiler and prompter of those proposals in postwar Europe in two issues of the French journal Aujourd´hui, art et architecture. The first of them published in May 1958, under the title “Cinquante ans de recherches dans le spectacle” collected the most important experiences in theory, scenography, technic, and theater architecture in the interwar period. Polieri worked with different architects in several projects for theater buildings, whose main feature was the mobility of all their elements and components, trying to get a dynamic experience during the performance. Those proposals related to Kinetic Art, were published in a second issue of Aujourd´hui, art et architecture entitled “Scénographie Nouvelle” in October 1963.